Current Research On Problem Posing : A Review - Kertiyani, Ni Made Intan; Azmi, Syahrul; Lu'luilmaknun, Ulfa (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
Teachers and students must learn how to pose problems effectively, hence there is a need for ongoing research on this topic. In order to identify the next topic that can be explored in the field of problem posing, this study aims to capture the latest research trends regarding problem posing over the last five years, starting from 2018-2023. The method used is Systematic Literature Review (SLR). The results of this study are research on problem posing widely spread in various topics, including a) theoretical considerations of problem posing, b) the relationship between problem posing and other abilities, c) analysis of teacher problem posing abilities, d) analysis of students' problem posing abilities and e) learning design to improve problem posing skills. These findings indicate that the problem posing has been extensively researched by scholars. The development of teaching materials that involve problem posing and learning design to enhance prospective teacher problem posing skill are two potential area of future research.